Twenty five years of the Journal of Travel & Tourism Marketing: a bibliometric ranking. Issue 9 (22nd November 2018) - Mulet-Forteza, Carles; Martorell-Cunill, Onofre; Merigó, José M.; Genovart-Balaguer, Juanabel; Mauleon-Mendez, Emilio
ABSTRACT: The Journal of Travel & Tourism Marketing ( JTTM ) is a leading international journal in "Marketing" and "Tourism, Leisure and Hospitality Management." JTTM published its first issue in 1992. In 2017, the journal has celebrated its twenty-fifth anniversary. For that reason, this study analyzes all the publications in the journal since its creation by using a bibliometric approach. The objective is to provide a complete overview of the main factors that affect the journal. This analysis includes key issues such as the distribution of annual publications and citations, the most cited papers, the h -index, citations per paper, the keywords that are mostly used, the influence on the publishing industry and authors, universities, and the countries that have the most publications. The paper uses the Scopus database to analyze the bibliometric data. Additionally, the paper also uses the visualization of similarities (VOS) viewer software to map graphically the bibliographic material. The graphical analysis uses bibliographic coupling, co-citation, citation, and co-occurrence of keywords. These results indicate that JTTM is one of the leading journals in the areas where the journal is indexed, with publications from a wide range of authors, institutions, and countries around the world.